A new approach for the determination of the linear elastic modulus from uniaxial tensile tests of sheet metals - Suttner, Sebastian; Merklein, Marion (Journal of Materials Processing Technology, 2017)
The determination of the linear elastic modulus is important for the numerical process design of forming operations. Test setups for the identification of the linear elastic modulus can be divided into dynamic methods like ultrasonic measurement and static methods like indentation tests or uniaxial tensile tests. Relevant standards recommend the determination of the linear elastic modulus via linear regression from stress vs. strain curves, while no information for an upper boundary exists. In this contribution, a new approach is presented, which uses the deformation work to identify a material-dependent upper boundary for the determination of the linear elastic modulus. The method is applied to two aluminum alloys AA5182-O and AA6016-T4, a deep drawing steel DX54, two advanced high strength steels HCT600X and HCT980X and a magnesium alloy AZ31B. The results confirmed a robust determination of the linear elastic modulus from the linear elastic behavior and a good reproducibility with a deviation below 5%. Moreover, with exception of AA5182-O, all investigated materials exhibit a quasi-elastic-plastic (QPE) transition between elastic and plastic material behavior.
LFT Import::2019-07-29 (2200)
Keywords: Elasticity; Material characterization; Young's modulus

An experimental and numerical investigation of different shear test configurations for sheet metal characterization - Yin, Qing; Zillmann, Benjamin; Suttner, Sebastian; Gerstein, Gregory; Biasutti, Manfredi; Tekkaya, A. Erman; Wagner, Martin F. -X.; Merklein, Marion; Schaper, Mirko; Halle, Thorsten; Brosius, Alexander (International Journal of Solids and Structures, 2014)
Simple shear tests are widely used for material characterization especially for sheet metals to achieve large deformations without plastic instability. This work describes three different shear tests for sheet metals in order to enhance the knowledge of the material behavior under shear conditions. The test setups are different in terms of the specimen geometry and the fixtures. A shear test setup as proposed by Miyauchi, according to the ASTM standard sample, as well as an in-plane torsion test are compared in this study. A detailed analysis of the experimental strain distribution measured by digital image correlation is discussed for each test. Finite element simulations are carried out to evaluate the effect of specimen geometries on the stress distributions in the shear zones. The experimental macroscopic flow stress vs. strain behavior shows no significant influence of the specimen geometry when similar strain measurements and evaluation schemes are used. Minor differences in terms of the stress distribution in the shear zone can be detected in the numerical results. This work attempts to give a unique overview and a detailed study of the most commonly used shear tests for sheet metal characterization. It also provides information on the applicability of each test for the observation of the material behavior under shear stress with a view to material modeling for finite element simulations. © 2013 Elsevier Ltd. All rights reserved.
LFT Import::2019-07-29 (1932)
Keywords: Heterogeneity; Sheet metal; Simple shear

An incremental analysis of a deep drawing steel’s material behaviour undergoing the predeformation using drawbeads - Schmid, Harald; Suttner, Sebastian; Merklein, Marion (IOP Conf. Series: Journal of Physics: Conf. Series 896 (2017) 011001, 2017)
LFT Import::2019-08-05 (2237)

Characterisation of kinematic hardening and yield surface evolution from uniaxial to biaxial tension with continuous strain path change - Merklein, Marion; Suttner, Sebastian; Brosius, Alexander (CIRP Annals - Manufacturing Technology, 2014)
With respect to multistage forming processes the material behaviour and the history of the strain path during the process is of special interest for the improvement of the numerical prediction of forming processes. While different researchers investigated the Bauschinger effect during a load reversal and biaxial loading with pre-strained specimens, in this paper the yield locus evolution in the first quadrant of the principles stress space under biaxial loading of a modified cruciform specimen without test interruption is presented. The movement of the yield surface centre caused by kinematic hardening is approximated by an alternative approach based on experimental results. © 2014 CIRP.
LFT Import::2019-07-29 (2026)
Keywords: Kinematic hardening; Sheet metal; Stress

Characterisation of strain rate dependency of sheet metals under biaxial loading with a strain rate controlled hydraulic bulge test - Lenzen, Matthias; Suttner, Sebastian; Merklein, Marion (7. WGP-Jahreskongress Aachen, 5.-6. Oktober 2017, 2017)
LFT Import::2019-08-05 (2247)

Characterization of the Bauschinger effect and identification of the kinematic Chaboche model by tension-compression tests and cyclic shear tests - Suttner, Sebastian; Merklein, Marion (Proc. International Deep Drawing Research Group Conf. IDDRG 2014, 2014)
LFT Import::2019-08-05 (2025)

Characterization of the shear stress state under non-proportional strain paths realized by biaxial stretching in the Marciniak Test - Suttner, Sebastian; Merklein, Marion (Materials Today: Proceedings, 2015)
Complex parts with sharp corners are on the rise to satisfy increasing customer demands on the design. To realize these parts in single or multistage forming processes the information of the material behavior under linear and non-linear strain paths is essential. As Bauschinger already showed for the material behavior under cyclic loading, a reduction of the subsequent beginning of plastic yielding can be observed. Different research works studied the Bauschinger effect under cyclic proportional loading or non-proportional strain paths mostly with uniaxial pre-straining of the material. In this paper the material behavior under shearing after previous biaxial stretching in the Marciniak test is analyzed for the aluminum alloy AA5182 and the advanced high strength steel DP600. The Marciniak test is suited for biaxial pre-straining due to an almost almost equibiaxial strain state and a homogeneous strain distribution in-plane on the bottom of the specimen up to higher strains than in a biaxial tensile test. The subsequent shear test is realized with a modified shear test specimen according to the ASTM standard. Finally, the influence of biaxal pre-straining on the beginning of plastic yielding under shear condition, the hardening behavior and the maximum reachable shear strain is investigated for a better understanding of the material behavior under non-proportional loading paths.
LFT Import::2019-07-29 (2101)
Keywords: Bauschinger effect; Material characterization; Non-linear strain paths

Charakterisierung des Verfestigungsverhaltens der Magnesiumlegierung AZ31 im Scherspannungszustand bei erhöhter Temperatur - Suttner, Sebastian; Merklein, Marion (Tagung Werkstoffprüfung 2015, 2015)
LFT Import::2019-08-05 (2124)

Charakterisierung und Modellierung des spannungszustandsabhängigen Werkstoffverhaltens der Magnesiumlegierung AZ31B für die numerische Prozessauslegung - Suttner, Sebastian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2017)
The use of light-weight materials, such as magnesium alloys, offers great potential in the area of sheet metal forming. In addition, the complex material behavior is to be modeled exactly in the process design. In the scope of the work, the stress statedependent material behavior of the magnesium alloy AZ31 B was investigated to improve the prediction accuracy of sheet metal forming processes. The focus of the investigations was the development, verification and validation of a novel material model for the consideration of anisotropic hardening at a forming temperature of 200° C. In order to determine the material characteristic under stretch forming, an innovative hydraulic bulge test (HB V) with online strain rate control by means of an optical strain measurement system was implemente

Cross-profile deep drawing of magnesium alloy AZ31 sheet metal for springback analysis under various temperatures - Suttner, Sebastian; Schmid, Harald; Merklein, Marion (18th International Conference on Sheet Metal, SHEMET 2019, 2019)
LFT Import::2019-08-05 (2363)

Cyclic tension test of AZ31 magnesium alloy at elevated temperature realized in a miniaturized uniaxial tensile test setup - Suttner, Sebastian; Merklein, Marion (Materials Science Forum, 2016)
The use of new materials, e.g. aluminum and magnesium alloys, in the automotive and aviation sector is becoming increasingly important to reach the global aim of reduced emissions. Especially magnesium alloys with their low density offer great potential for lightweight design. However, magnesium alloys are almost exclusively formable at elevated temperatures. Therefore, material characterization methods need to be developed for determining the mechanical properties at elevated temperatures. In particular, cyclic tests at elevated temperatures are required to identify the isotropic-kinematic hardening behavior, which is important for numerically modeling the springback behavior. In this contribution, a characterization method for determining the cyclic behavior of the magnesium alloy AZ31B at an elevated temperature of 200 °C is presented. The setup consists of a miniaturized tensile specimen and stabilization plates to prevent buckling under compressive load. The temperature in the relevant area is introduced with the help of conductive heating. Moreover, the complex kinematic model according to Chaboche and Rousselier is identified, to map the transient hardening behavior of AZ31B after load reversal, which cannot be modeled with a single Bauschinger coefficient.
LFT Import::2019-07-29 (2186)
Keywords: Bauschinger effect; Characterization; Cyclic testing; Magnesium alloy

Einfluss der Auflösung des Dehnungsfeldes auf die Kennwertermittlung im Scherzugversuch von Aluminium- und Magnesiumlegierungen - Lenzen, Matthias; Suttner, Sebastian; Merklein, Marion (Tagung Werkstoffprüfung 2016, 2016)
LFT Import::2019-08-05 (2194)

Evaluation of kinematic hardening models for multiple stress reversals under continuous cyclic shearing and multi - step bending - Rosenschon, Martin; Suttner, Sebastian; Merklein, Marion (LS-DYNA Forum 2015, 2015)
LFT Import::2019-08-05 (2125)

Evolution of yield loci for aluminum alloy AA6016 and deep drawing steel DC06 under the influence of non-linear strain paths - Merklein, Marion; Suttner, Sebastian (Key Engineering Materials, 2013)
The application of modern materials plays an important role directly under the aspect of lightweight potential. To exploit these options effectively a numerical accurate reproduction of the material behavior is indispensable. Especially in the case of large deformations a directional and strain rate dependent hardening behavior can be observed. By disregarding this effect significant failure in the computed stress state can arise, which can conduct to a corruption of the spring-back forecast. Within this contribution a new test method for analyzing the evolution of subsequent yield loci under strain path changes for the aluminum alloy AA6016 and the deep drawing steel DC06 is presented. In the first stage of the experimental investigations, yield loci with linear strain paths were considered to characterize the material behavior for the initial condition. On further experiments with several stress states the strain path dependent hardening behavior of the material is determined. The non-linear strain paths are realized through uniaxial prestrained primary specimens with following extraction of secondary samples for following stress states, e.g. a modified ASTM simple shear test specimen. Subsequent yield loci are investigated and compared to the yield surfaces Hill'48 and Barlat 2000 (Yld2000-2d) with an isotropic hardening behavior. With this study the evolution of the yield locus for prestrained specimens is evaluated. The research of the subsequent yield loci for strain path changes serves as basis for further scientific investigations with a view to assess different approaches of isotropic-kinematic hardening models in consideration of the analyzed steel and aluminum sheet metals. © (2013) Trans Tech Publications.
LFT Import::2019-07-29 (1852)
Keywords: Hardening behavior; Simple shear test; Strain path changes; Yield locus evolution

Experimental and numerical investigation of a strain rate controlled hydraulic bulge test of sheet metal - Suttner, Sebastian; Merklein, Marion (Journal of Materials Processing Technology, 2016)
LFT Import::2019-07-29 (2185)
Keywords: Constant strain rate; Hydraulic bulge test; Material characterization; Metal forming

Experimental Investigation and Numerical Modeling of the Bond Shear Strength of Multi-layered 6000 Series Aluminum Alloys - Herrmann, Jürgen; Suttner, Sebastian; Merklein, Marion (Procedia Engineering, 2017)
The use of high-strength aluminum alloys is one key factor for the realization of lightweight design in industrial applications. Besides alloying, it is possible to produce high-strength sheet materials using the Accumulative Roll Bonding (ARB) process. Based on a repetitive stacking and roll bonding process, multi-layered sheets with a nanocrystalline grain structure are produced. The bond formation is created by a cold welding process due to the high pressure in the rolling gap and cracks in the oxide film of the aluminum sheet material caused by the thickness reduction. The experimental investigation of the bond strength is crucial for the assessment of the formability of the multi-layered sheet material. High bonding quality is necessary in order to prevent failure mechanisms like delamination in subsequent forming operations. Furthermore, a numerical model, which contains discrete layers over the sheet thickness as well as their bonding mechanisms will be implemented in finite element analysis. This enables a process layout for forming operations by the prediction of delamination effects. Within this investigation, an experimental test method is presented to characterize the bond shear strength of multi-layered sheet material. The use of an optical strain measurement system enables the identification of the material behavior over the sheet thickness during the shear test. For this investigation a 16-layered aluminum alloy AA6014 is used. However, the bond shear strength of the last bonded respectively middle layer of the sheet material is investigated. The 16-layered material has 15 bonds over the thickness but the one in the middle has the lowest bond strength as it was only roll bonded once compared to the others, which were rolled at least twice. The bonding mechanisms are modelled using a tiebreak contact formulation in the finite element software LS-DYNA. Concluding, the numerical model is validated by comparison with the experimental results.
EAM Import::2019-03-14

Experimental investigation of Ti-6Al-4V with a biaxial tensile test setup at elevated temperature - Merklein, Marion; Suttner, Sebastian; Schaub, Adam (Key Engineering Materials, 2014)
The requirement for products to reduce weight while maintaining strength is a major challenge to the development of new advanced materials. Especially in the field of human medicine or aviation and aeronautics new materials are needed to satisfy increasing demands. Therefore the titanium alloy Ti-6Al-4V with its high specific strength and an outstanding corrosion resistance is used for high and reliable performance in sheet metal forming processes as well as in medical applications. Due to a meaningful and accurate numerical process design and to improve the prediction accuracy of the numerical model, advanced material characterization methods are required. To expand the formability and to skillfully use the advantage of Ti-6Al-4V, forming processes are performed at elevated temperatures. Thus the investigation of plastic yielding at different stress states and at an elevated temperature of 400°C is presented in this paper. For this reason biaxial tensile tests with a cruciform shaped specimen are realized at 400°C in addition to uniaxial tensile tests. Moreover the beginning of plastic yielding is analyzed in the first quadrant of the stress space with regard to complex material modeling.
LFT Import::2019-07-29 (2018)
Keywords: Formability; High performance metals; Sheet metal forming

Experimentelle Untersuchung des zweiachsigen Spannungszustands im Kreuzzugversuch zur Identifikation von Werkstoffmodellen für die Finite-Elemente Simulation - Suttner, Sebastian; Merklein, Marion (Tagungsband Werkstoffprüfung, 2013)
LFT Import::2019-08-05 (1920)

Influence of specimen size and sheet thickness on the material behavior of AZ31B under uniaxial tension - Suttner, Sebastian; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2016)
Concerning a low specific density, magnesium alloys offer a great potential to reduce the part weight. Due to the conditional formability of magnesium alloys at room temperature, forming processes are mostly realized at elevated temperatures. Within this contribution, uniaxial tensile tests for two different specimen geometries with a gauge length of 50 mm and 2 mm and a cross section of 12.5×1 mm2 and 2×1 mm2 are carried out for the magnesium alloy AZ31B at an elevated temperature of 200 °C. Since the specimen size is reduced, the influence of the sheet thickness needs to be analyzed. The analysis of the sheet thickness results in a change of the determined flow curve above a strain level of 0.1 and a much earlier failure of specimen with an initial sheet thickness of 1.5 mm. The changed material behavior can be explained by a different microstructure, e.g. the influence of the grain size. In summary, a characterization of the magnesium alloy AZ31B at elevated temperatures can be realized with a miniaturized test setup.
LFT Import::2019-07-29 (2212)

Influence of stress relaxation after uniaxial pre-straining on subsequent plastic yielding in the uniaxial tensile test of sheet metal - Suttner, Sebastian; Merklein, Marion (Key Engineering Materials, 2015)
Resource efficiency, design oriented accuracy and lightweight properties are demands on modern sheet metal forming parts in the automotive sector. The use of new materials leads to additional challenges on the numerical design of forming processes. During these forming processes the material undergoes different strain states that cause non-linear strain paths. Since the numerical prediction highly depends on the identified characteristic values of the material, an exact characterisation of the material behaviour is essential. Especially obtuse angles of the stress vector trigger a recovery of the material by returning stress. Besides, a relaxation of the material is investigated during holding a constant strain level. The effect of relaxation lead to an altered material behaviour that appears in a reduction of the beginning of plastic yielding. In addition, a kinematic hardening behaviour as under cyclic loading and load reversal, known as the Bauschinger effect, occurs after the relaxation of the stress and results in a reduced beginning of plastic yielding by loading in the same direction as the introduced pre-strain. Within this research work the effect of relaxation is investigated for two materials, AA5182 and DP600, with an initial sheet thickness of 1.0 mm. These materials are typically used for internal and accordingly functional parts in the automotive sector. The relaxation of the material is analysed with different holding times of a constant pre-strain at different levels of straining. The release of the material is studied by subsequent uniaxial tensile tests after pre-straining with the same load condition. Moreover, the influence of the named effects is shown by comparison of the translation of the yield loci.
LFT Import::2019-07-29 (2093)
Keywords: Metal forming; Modelling; Relaxation

Investigation of process induced changes of material behaviour using a drawbead in forming operations - Schmid, Harald; Suttner, Sebastian; Merklein, Marion (7. WGP-Jahreskongress Aachen, 5.-6. Oktober 2017, 2017)
LFT Import::2019-08-05 (2249)

Investigation of the beginning of plastic yielding and the hardening behaviour under biaxial tension - Suttner, Sebastian; Kuppert, Andreas (Advanced Materials Research, 2013)
The main focus of the experimental observation deals with the investigation of the plastic yielding of DC06 and DP600 under biaxial tension in comparison to an identified material model with an isotropic hardening behaviour. The isotropic hardening law describes the hardening behaviour of the material by application and approximation of the flow curve. Prevalent hardening laws are proposed by Swift (1952) or Hockett and Sherby (1975) and lead to an expansion of the yield surface in the stress space. By reasons of good accordance in an earlier survey the given materials are modeled by the yield criterion Yld2000-2d and the isotropic hardening law of Swift. In this case the yield loci at different experimental states of plastification are compared with the yield loci given from the isotropic expansion of the Yld2000-2d yield surface. Furthermore a possible approach for modelling the change of the yield criterion's shape in the stress space during plastification is shown. With respect to further investigations additional research work is needed including extended and complex hardening laws to describe the real material behaviour sufficiently. © (2013) Trans Tech Publications, Switzerland.
LFT Import::2019-07-29 (1892)
Keywords: Material characterisation; Metal forming; Modelling

Investigation of the Potential for the Fabrication and Forming of Adaptronic Semi-finished Parts Joined by Cold Formed Pin Structures - Kraus, Martin; Suttner, Sebastian; Merklein, Marion (2ND INTERNATIONAL CONFERENCE ON ADVANCED JOINING PROCESSES (AJP 2021), 2021)

Investigation of the Springback Behaviour of High-strength Aluminium Alloys Based on Cross Profile Deep Drawing Tests - Hetz, Peter; Suttner, Sebastian; Merklein, Marion (Procedia Manufacturing, 2020)
The prediction of springback of sheet metal parts is still a challenge in metal forming processes. To meet the requirements for dimensional accuracy of a sheet metal part, the springback must be compensated and the production process has to be designed accordingly. During forming, elastic energy is stored in the semi-finished product. When removing a part from the deep-drawing tool, the resulting residual stresses with an elastic component cause unwanted changes of the part`s geometry in forming. Especially sheet materials with low elastic modulus and high yield strength tend to an increased springback. Among others, these materials include aluminium alloys of the 7000 series. For this reason, a fundamental understanding of the material behaviour of these materials is relevant for designing a sheet metal forming process. This contribution uses a novel approach to investigate the springback behaviour of AA7020-T6 and AA7075-T6. For this purpose, cross profiles are deep-drawn with various parameter settings and subsequently digitised with a three-dimensional optical measurement system. By analysing the digitised profiles, the springback behaviour is quantified depending on the experimental parameters. Due to the right-angled structure of the cross profile, the influence of anisotropy in 0 and 90 degree to rolling direction is investigated within one forming operation.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Cross profile; Deep drawing; High-strength aluminium alloys; Springback compensation

Investigation of the Unloading Yield Effect in Aluminum and Magnesium Sheet Metal Alloys at Room Temperature - Degner, Julia; Suttner, Sebastian; Merklein, Marion (Key Engineering Materials, 2016)
LFT Import::2019-07-29 (2178)
Keywords: Advanced Lightweight Materials; Material Characterization; Unloading Yield

Magnesium - Leichtbauwerkstoff der Blechumformung: Relevanz einer exakten Werkstoffcharakterisierung und -modellierung - Suttner, Sebastian; Merklein, Marion (Konstruktion, 2016)
LFT Import::2019-07-29 (2192)

Manufacturing of Innovative Aluminum Components by Combining Shear Cutting Operation and Tailor Heat Treated Blank Technique - Degner, Julia; Suttner, Sebastian; Tsoupis, Ioannis; Lechner, Michael; Merklein, Marion (5th International Conference on Accuracy in Forming Technology, 2015)
LFT Import::2019-08-05 (2130)

Mechanical Weld Zone Characterization for the Numerical Simulation of Forming Friction Stir Welded Aluminum Blanks - Gnibl, Tobias; Suttner, Sebastian; Merklein, Marion (AIP Conference Proceedings, 2013)
LFT Import::2019-07-29 (1942)

Methodik zur Parameteridentifikation des kinematischen Verfestigungsmodells nach Chaboche und Rousselier - Suttner, Sebastian; Rosenschon, Martin; Merklein, Marion (Tagungsband Werkstoffprüfung, 2014)
LFT Import::2019-08-05 (2061)

Über die Blechprüfung von heute - Merklein, Marion; Suttner, Sebastian; Hofmann, Maren; Kuppert, Andreas (Tagungsband Werkstoffprüfung, 2012)
LFT Import::2019-08-05 (1839)

Validation of kinematic hardening parameters from different stress states and levels of plastic strain with the use of the cyclic bending test - Rosenschon, Martin; Suttner, Sebastian; Merklein, Marion (Key Engineering Materials, 2015)
The recent development of new lightweight sheet metal materials, like advanced highstrength steels or aluminium alloys, in combination with an increasing component complexity provides new challenges to the numerical material modelling in the FEM based process design. An auspicious approach to improve the quality of the numerical results - most notably in springback analysis - is the modelling of the so called Bauschinger effect achieved through implementation of kinematic hardening models. Within this paper the influence of the stress state and the level of prestrain on the numerical simulation result of the advanced high strength steel DP-K45/78+Z will be analysed. For this purpose, a parameter identification of the kinematic hardening law according to Chaboche and Rousselier is performed at different pre-strains on the basis of experimental data from tension-compression tests as well as cyclic shear tests. Finally, the identified parameters are validated in a comparison between numerical and experimental results of a cyclic bending test.
LFT Import::2019-07-29 (2089)
Keywords: Kinematic hardening; Metal forming; Modelling

Werkstoffcharakterisierung mit Blick auf die Vergangenheit, die Gegenwart und die Zukunft - Merklein, Marion; Suttner, Sebastian (Tagungsband - 20. Sächsiche Fachtagung Umformtechnik, 2013)
LFT Import::2019-08-05 (1921)